The effect of velocity on flight phase duration in race walking: a comparative study of three cases - Bernans, E.; Saulgriezis, R. (Journal of Physical Education and Sport, 2023)
The conventional race walking technique adheres to competition rules by excluding a noticeable flight phase visible to the human eye. However, race walkers often exhibit a slight flight phase, sparking an ongoing debate: Is the flight phase permissible? Is it acceptable if the referee fails to detect it? Is the flight phase an inherent part of the race walking technique that cannot be eliminated? The objective of this study was to examine the characteristics of the flight phase in race walking at different speeds. Additionally, the study aimed to compare the performance of individuals in the 20-km distance with the average TOP10 male results from three Olympic games, as well as Y. Suzuki's world record. All participants completed three race walking trials on a level treadmill, with the trials conducted in a randomized order. The walking kinematics were observed using the Optojump Next optical system. Our study revealed that race walkers were able to maintain flight time duration below the threshold of 0.04 s, which is the upper limit undetectable by the human eye, at their competition velocity. However, the impact on flight time varied at higher velocities. Double support steps were rare, occurring less than 2% of the time during race walking at competition velocity. Our findings highlight the importance of keeping the flight phase within specified threshold levels to ensure compliance with competition rules. Further research and potential implementation of electronic control systems may enforce these rules and provide valuable insights for athletes, coaches, and spectators.